Identifikasi Site Strategis Arsitektur Amfibi di Area Rawan Banjir Palembang, Indonesia - Harrini Mutiara Hapsari Wahyu; Rizka Drastiani; Almira Ulfa (Archvisual: Jurnal Arsitektur dan Perencanaan, 2022)
Urban flooding that is occuring currently in several megacities in the world is a well-known event, this event is also happening in the City of Palembang. Annual floods that occur in Palembang are common and natural Nevertheless, these frequent floods have a negative impact, devastative, and threaten the well-being of the lives of local residents, especially in several flood-prone areas on the Musi riparian and Musi tributaries. Several disaster management structures have been studied to minimize errors, one of which is by implementing the Amphibious Architecture in residential buildings. This study aims to identify strategic locations that meet the building criteria for Amphibious Houses to help residents adapt to flooding with adaptive design. A SWOT analysis was conducted which aims to determine the most strategic location for amphibious architecture according to the highest scoring results. Scoring is done by assigning a value of 8 variables to seven flood-prone locations in Palembang. Those variables are: strengths (suitable flood heights and new developments); weaknesses (inappropriate flood heights and land use); opportunities (suitability of land for the application of amphibious structures and other structures); and threats (costs and introduction of new structural systems to the community). The conclusions of this paper are expected to contribute in the implementation of Amphibious Architecture in flood disaster mitigation system in Palembang.